Estimating Risk of Multiple Sclerosis Disease Reactivation in Pregnancy and Postpartum: The VIPRiMS Score - Bsteh, Gabriel; Hegen, Harald; Riedl, Katharina; Altmann, Patrick; Di Pauli, Franziska; Ehling, Rainer; Zulehner, Gudrun; Rommer, Paulus; Leutmezer, Fritz; Deisenhammer, Florian; Berger, Thomas (Frontiers in Neurology, 2022)
Background: Evidence guiding personalized decision-making regarding disease-modifying therapy (DMT) around pregnancy in relapsing multiple sclerosis (RMS) is lacking. Objective: To generate and validate a risk score for disease reactivation intrapartum and postpartum in RMS. Methods: From the Vienna Innsbruck MS database (VIMSD), we included 343 pregnancies in RMS patients. Primary endpoint was disease reactivation. Patients were randomly assigned 2:1 in a generation and validation dataset. A predictive score was calculated using Cox regression and validated. Results: In the generation dataset, occurrence of relapse and type of DMT in the year before conception, DMT wash-out duration, EDSS at conception and time until DMT restart postpartum were identified as independent predictors of disease reactivation (all p<0.001). The resulting 10-point risk score robustly predicted reactivation (explaining 75% of variance, p<0.001) identifying patients at high (≥6 points; mean risk 65%; range 50-100%; hazard ratio [HR] 14.5), intermediate (3-5 points; mean risk 24%; range 15-35%; HR 4.3) and low risk (≤2 points: mean risk 6%; range 0-8%) of disease reactivation in pregnancy and up to 6 months postpartum. Conclusions: The composite VIPRiMS score is a valuable clinical tool to support patients and neurologists in anticipating risk and, thus, individualizing treatment decision-making around pregnancy.